1979
DOI: 10.1073/pnas.76.12.6622
|View full text |Cite
|
Sign up to set email alerts
|

Production of choriogonadotropin-like factor by a microorganism.

Abstract: Extracts from an acetone powder preparation of a culture of a microorganism tentatively named Progenitor cryptocides contain choriogonadotropin (CG-like factor as determined by radioimmunoassay with antiserum to human (h)CG # subunit COOH-terminal peptide and radioreceptor assay with bovine corpus luteum membranes. Possible interference by proteases in the extracts was excluded. Immunoreactive materials reacting with antisera to hCG 0 subunit and hCG P subunit COOH-terminal peptide were also found in the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 26 publications
(18 reference statements)
3
24
0
1
Order By: Relevance
“…Almost all ofthe immunoreactive ,3endorphin detected exhibited a molecular weight >28,000. The distribution of immunoreactive (3-endorphin was qualitatively similar to that of the multiple high molecular weight forms seen in the column Migration, cm DISCUSSION Recent studies have demonstrated material similar to mammalian insulin in unicellular eukaryotes and prokaryotes (a protozoan, two fungi, and a bacterium) (3), as well as material similar to the placental form of human chorionic gonadotropin in a bacterium (15). In the present study, we found material in extracts ofT.…”
Section: Methodssupporting
confidence: 63%
See 2 more Smart Citations
“…Almost all ofthe immunoreactive ,3endorphin detected exhibited a molecular weight >28,000. The distribution of immunoreactive (3-endorphin was qualitatively similar to that of the multiple high molecular weight forms seen in the column Migration, cm DISCUSSION Recent studies have demonstrated material similar to mammalian insulin in unicellular eukaryotes and prokaryotes (a protozoan, two fungi, and a bacterium) (3), as well as material similar to the placental form of human chorionic gonadotropin in a bacterium (15). In the present study, we found material in extracts ofT.…”
Section: Methodssupporting
confidence: 63%
“…This material (apparent molecular weight -4500) is similarly reactive with two anti-ACTH antisera, one specific for the ACTH- (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) sequence and the other specific for sequences 1-14 and 17-39. Further, this material also exhibits activity in the ACTH bioassay with a mean immunoassay/ bioassay ratio of 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using sensitive and specific assay methods a systematic search has revealed the presence of CG-like material in neoplastic cells of all experimental animal tumors that have been tested in vitro and in vivo [4], in a wide variety of cultured cells, sections and/or touch imprints of human malignant neoplasms [8,12,16], in spermatozoa [1,5] and in several strains of some species of bacteria isolated from cancer patients [2,3,11].…”
Section: Introductionmentioning
confidence: 99%
“…The hCG and LH-like molecules have been found in lower organisms, which suggests that these molecules, performing different functions, have been conserved during the evolution. [8][9][10][11][12] 2.…”
Section: Introductionmentioning
confidence: 99%